Cerebrospinal Fluid Shunt-Associated Surgical Site Infection With Three- Versus Twelve-Month Follow-Up in Canadian Hospitals. (October 2020) - Choi, Kelly Baekyung; Conly, John; Chow, Blanda; Embree, Joanne; Lee, Bonita; Lefebvre, Marie-Astrid; Mitchell, Robyn; Pelude, Linda; Shephard, Allyson; PHAC, CNISP; Comeau, Jeannette
Abstract : Background: Surgical site infection (SSI) after cerebrospinal fluids (CSF) shunt surgery is thought to be acquired intraoperatively. Biomaterial-associated infection can present up to 1 year after surgery, but many national systems have shortened follow-up to 90 days. We compared 3- versus 12-month follow-up periods to determine the nature of case ascertainment in the 2 periods. Methods: Participants of any age with placement of an internal CSF shunt or revision surgical manipulation of an existing internal shunt identified in the Canadian Nosocomial Infection Surveillance Program (CNISP) participating hospitals between 2006 and 2018 were eligible. We excluded patients with external shunting devices or culture-positive CSF at the time of surgery. Patients were followed for 12 months after surgery for the primary outcome of a CSF infection with a positive CSF culture by review of laboratory and health records. Patients were categorized as adult (aged ≥18 years) or pediatric (aged < 18 years). The infection rate was expressed as the number of CSF shunt-associated infections divided by the number of shunt surgeries per 100 procedures. Results: In total, 325 patients (53% female) met inclusion criteria in 14 hospitals from 7 provinces were identified. Overall, 46.1% of surgeries were shunt revisions and 90.3% of shunts were ventriculoperitoneal. For pediatric patients, the median age was 0.7 years (IQR, 0.2–7.0). For adult patients, the median age was 47.9 years (IQR, 29.6–64.6). The SSI rates per 100 procedures were 3.69 for adults and 3.65 for pediatrics. The overall SSI rates per 100 procedures at 3 and 12 months were 2.74 (n = 265) and 3.48 (n = 323), respectively. By 3 months (90 days), 82% of infection cases were identified (Fig. 1). The median time from procedure to SSI detection was 30 days (IQR, 10–65). No difference was found in the microbiology of the shunt infections at 3- and 12-month follow-ups. The most common pathogens were coagulase-negative Staphylococcus (43.6 %), followed by S. aureus (24.8 %) and Propionibacterium spp (6.5 %). No differences in age distribution, gender, surgery type (new or revision), shunt type, or infecting organisms were observed when 3- and 12-month periods were compared. Conclusions: CSF-SSI surveillance for 3 versus 12 months would capture 82.0% (95% CI, 77.5–86.0) of cases, with no significant differences in the patient characteristics, surgery types, or pathogens. A 3-month follow-up can reduce resources and allow for more timely reporting of infection rates. Funding: None Disclosures: None